68Ga-PSMA PET/CT Scan on Postoperative Assessment of Sinonasal Glomangiopericytoma. (September 2021) - Sakthivel, Pirabu; Kumar, Arunav; Arunraj, Sreedharan Thankarajan; Singh, Chirom Amit; Kumar, Rakesh
Abstract : Abstract: Prostate-specific membrane antigen (PSMA) is expressed on the endothelial cells of tumor-associated neovasculature of various nonprostatic benign and malignant neoplasms. Positive intense uptake on PET/CT imaging with 68 Ga-labeled PSMA is noted in a patient with sinonasal glomangiopericytoma, and the same is noted to be absent following complete surgical excision. 68 Ga-PSMA PET/CT may be a useful tool for early recurrence identification, differentiating recurrence from surgical site reparative tissues, and peptide receptor radionuclide therapy of residual lesions.